Disentangling the Anacondas: Revealing a New Green Species and Rethinking Yellows † - Rivas, Jesús (2024)
Anacondas, genus Eunectes, are a group of aquatic snakes with a wide distribution in South America. The taxonomic status of several species has been uncertain and/or controversial. Using genetic data from four recognized anaconda species across nine countries, this study investigates the phylogenetic relationships within the genus Eunectes. A key finding was the identification of two distinct clades within Eunectes murinus, revealing two species as cryptic yet genetically deeply divergent. This has led to the recognition of the Northern Green Anaconda as a separate species (Eunectes akayima sp. nov), distinct from its southern counterpart (E. murinus), the Southern Green Anaconda. Additionally, our data challenge the current understanding of Yellow Anaconda species by proposing the unification of Eunectes deschauenseei and Eunectes beniensis into a single species with Eunectes notaeus. This reclassification is based on comprehensive genetic and phylogeographic analyses, suggesting closer relationships than previously recognized and the realization that our understanding of their geographic ranges is insufficient to justify its use as a separation criterion. We also present a phylogeographic hypothesis that traces the Miocene diversification of anacondas in western South America. Beyond its academic significance, this study has vital implications for the conservation of these iconic reptile species, highlighting our lack of knowledge about the diversity of the South American fauna and the need for revised strategies to conserve the newly identified and reclassified species.